2006
DOI: 10.1111/j.1365-2648.2006.04057.x
|View full text |Cite
|
Sign up to set email alerts
|

Somali and Oromo refugee women: trauma and associated factors

Abstract: These findings suggest a need for nurses, and especially public health nurses who work with refugee and immigrant populations in the community, to develop a more comprehensive understanding of the range of refugee women's experiences and the continuum of needs post-migration, particularly among older women with large family responsibilities. Nurses, with their holistic framework, are ideally suited to partner with refugee women to expand their health agenda beyond the biomedical model to promote healing and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 55 publications
2
66
0
1
Order By: Relevance
“…There are high levels of stigma around addressing mental health in the Somali community 3 and therefore a lack of culturally options to address such concerns 12 . Concerns about emotional health may become what one study focusing on Somali women described as "silent worries," as women deal with unexpressed loss and distress 13 , alongside high levels of previous exposure to trauma 14 .…”
Section: Introductionmentioning
confidence: 99%
“…There are high levels of stigma around addressing mental health in the Somali community 3 and therefore a lack of culturally options to address such concerns 12 . Concerns about emotional health may become what one study focusing on Somali women described as "silent worries," as women deal with unexpressed loss and distress 13 , alongside high levels of previous exposure to trauma 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The troubling aspect is that these feelings or "the old present" as Margaret Wilkinson calls it (2010, p. 4), can be transmitted from one generation to another via mirror neurons (Cozolino, 2010;Farmer, 2009;Nunn et al, 2008). Some say the presence of intergenerational trauma transference can have an impact on the lives and future of Somali-Canadian youth.…”
Section: My Research Interest In Resettled Refugees and Somali-canadimentioning
confidence: 99%
“…To understand these patterns of trauma within the Canadian Somali community, I read other Somali Diaspora studies such as Schwerdtfege and Goff (2007) and Robertson et al (2006) who conducted their research in UK and the US Somali communities to help me understand and explain how trauma, migration and past ordeals are transposed from one generation to the next. Furthermore, in my own study I linked cutting-edge neurobiological analysis of trauma and healing methods including the process of Neuroplasticity.…”
Section: My Research Interest In Resettled Refugees and Somali-canadimentioning
confidence: 99%
“…Jaranson et al [14] highlighted the need to recognize the prevalence of torture among African refugees, particularly women who were tortured at the same rates as men, and develop appropriate resources. Women who reported higher levels of trauma were older, had more family responsibilities, less education, and were less likely to speak English [15]. Shannon, O'Dougherty, and Mehta [16] found that in a sampling of refugees in the Midwest two-thirds had never discussed their history of trauma with their physicians, and that their physicians had never asked.…”
Section: Theoretical Frameworkmentioning
confidence: 99%